Regionalism, multilateralism, and deeper integration - Lawrence, Robert Z., 1949- (Brookings Institution, 1996)
Over the past decade, international economic liberalization has been pursued through both multilateral and regional arrangements. In the Uruguay Round, more than one hundred governments pledged their commitment to greater open trade in goods and services, and established new rules under the enforcement of the World Trade Organization. At the same time, however, many regional arrangements have been negotiated - including the European Union and the North American Free Trade Agreement. Nonetheless, controversy still rages about these arrangements. Are regional arrangements stumbling blocks or, in fact, building blocks for a more integrated and successful international economy? In this book, part of the Brookings Integrating National Economies series, Robert Z. Lawrence addresses this question and explains both sides of the raging debate.
Keywords: International economic integration -- Case studies.; Regionalism -- Case studies.; Free trade -- Case studies.; Intégration économique internationale -- Études de cas.; Régionalisme -- Études de cas.; Libre-échange -- Études de cas.; BUSINESS & ECONOMICS -- International -- General.; BUSINESS & ECONOMICS -- International -- Economics.; Free trade; International economic integration; Regionalism; POLITICAL SCIENCE / International Relations / Diplomacy; Case studies